Coarticulació i assimilació en fonologia. Dades de moviment lingual sobre els grups consonàntics amb C2=/d/ en català - Recasens, Daniel (Caplletra. Revista Internacional de Filologia, 1995)
This paper uses the electromagnetic midsagittal articulometry technique (EMMA) for the investigation of tongue tip and tongue blade activity during the production of Catalan clusters consisting of consonants specified for adjacent places of articulation. C2 of these clusters is /d/ (a dental in Catalan); C1 is either an alveolar (/1/, /n/, /r/, /z/), a post-alveolar (/?/) or an alveopalatal (/?/). Apical and laminal trajectories for these clusters are compared to those for intervocalic /d/ and for intervocalic C 1. Data show the presence of a single dental articulation for /nd/ and /1d/ and of two sequential articulatory places (alveolar for Cl and dental for C2) in the case of the cluster /rd/. The clusters /zd/ and /?d/ are produced with an alveolar place followed by an intermediate place between the dental and the alveolar zone, which indicates progressive co-articulatory effects (or even progressive assimilation) from Cl fricative onto C2=/d/. Finally, the production of the sequence /?d/ involves presumably gestural blending resulting into an intermediate location between that for C1 and that for C2. The notion of «articulatory constraint» is discussed in the light of these results.